THE EVOLUTION OF JOHN HENRY NEWMANâS SPIRITUALITY - Ola, Dominikus Doni (Universitas Katolik Santo Thomas Sumatera Utara, 2011)
John Henry Newman is an outstanding pupil. He had a great desire for knowledge, falls in love with music, poem and expressed his thought in speech and writing, always ready for wonder, wholly hearted and entirely ready to the call of everything around him, loved solitude, and ready to seek the Lord will provide in every changes in the external circumstances of life. For Newman, Evangelical teaching had been a great blessing for England and had led him to a spiritual life. Together with his knowledge of the doctrine of Calvinism and Catholic delivered Newman in a big conflict of his mind in one side, but in another side he looked it as a source of a personal encounter with God. Since the first conversions of 1816, Newman who has a sharp consciousness of the realities of the world beyond knew that he was powerless without Divine assistance.